Strengthening networks: A social network intervention among higher education teachers. (February 2018) - Van Waes, Sara; De Maeyer, Sven; Moolenaar, Nienke M.; Van Petegem, Peter; Van den Bossche, Piet
Abstract: Teachers' opportunities to learn at the workplace are shaped by the relationships in which they discuss their instructional practice, what we call teaching networks . This study examined the extent to which such teaching networks could be strengthened during a professional development (PD) program. An intervention was designed to evaluate whether the development of teaching networks was affected in terms of network composition and access to teaching content. Longitudinal ego-network data of Belgian university teachers (N = 38, 1670 ties) were collected over a two-year time period. Multilevel analyses showed that the intervention group developed larger networks and increased network dynamics, compared to the control group. The intervention group also developed more diverse networks, and showed increased access to teaching content, suggesting that the intervention changed teachers' networks over time. This study shows the potential of network interventions to support teachers' professional development, and of network analysis as a tool to analyze professional relations. Highlights: An intervention was designed to strengthen teaching networks during a PD program. Ego-network data were collected over two-years from university teachers. The intervention group showed enlarged networks and increased network dynamics. The intervention group developed more diversely composed teaching networks. The intervention group consulted a wider teaching network for information and advice.